2021
DOI: 10.5187/jast.2021.e66
|View full text |Cite
|
Sign up to set email alerts
|

Dietary inclusion of glucose oxidase supplementation to corn-wheat-based diet enhance growth performance, nutrient digestibility, blood profile of lactating sows

Abstract: Dietary inclusion of glucose oxidase supplementation to corn-wheatbased diet enhance growth performance, nutrient digestibility, blood profile of lactating sows Running Title (within 10 words)Effect of glucose oxidase on lactating sows

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 44 publications
1
5
0
Order By: Relevance
“…Previous study found that 120 mg/kg macleaya extract (a standardized premixture of MCE) increased weight gain and nutrient digestibility of piglets (23). Sureshkumar et al reported that the ADG were significantly increased in piglets fed diet supplemented with 400 U/kg glucose oxidase (24). In the present study, MCE and GOD compound additives significantly increased ADG and decreased F/G, but did not change ADFI in piglets.…”
Section: Discussionsupporting
confidence: 54%
“…Previous study found that 120 mg/kg macleaya extract (a standardized premixture of MCE) increased weight gain and nutrient digestibility of piglets (23). Sureshkumar et al reported that the ADG were significantly increased in piglets fed diet supplemented with 400 U/kg glucose oxidase (24). In the present study, MCE and GOD compound additives significantly increased ADG and decreased F/G, but did not change ADFI in piglets.…”
Section: Discussionsupporting
confidence: 54%
“…This inconsistency might result from the differences in pathogen serotype and dosage or the number of times oral ETEC administration. Previously, supplemental GOD was indicated to improve growth performance in pigs under non-infection conditions ( Tang et al, 2016 ; Dang et al, 2021 ; Sureshkumar et al, 2021 ). However, it is unknown whether GOD could protect piglet growth against infection.…”
Section: Discussionmentioning
confidence: 99%
“…(3) Generation of hydrogen peroxide catalyzed by GOD is favorable for defending against bacterial invasion due to its broad-spectrum antibacterial effect (Murphy and Friedman, 2019). Previously, several studies have validated the positive effects of GOD addition on growth performance and gut health in chickens (Wu et al, 2019(Wu et al, , 2020Meng et al, 2021) and pigs (Tang et al, 2016;Dang et al, 2021;Sureshkumar et al, 2021) under the non-challenge condition. Moreover, GOD might be profitable for guarding against bacterial infection, as supported by the study of Zhao et al (2022) who observed that GOD addition attenuated Clostridium perfringens-induced necrotic enteritis of broilers by improving intestinal structure and functions.…”
Section: Introductionmentioning
confidence: 99%
“…4 Body weight difference: Initial to Farrowing; 2, Farrowing to Weaning; 3, Weaning to Ovulation. 5 Backfat thickness difference: Initial to Farrowing; 2, Farrowing to Weaning; 3, Weaning to Ovulation. ADFI, average daily feed intake.…”
Section: Reproduction Performance Of Sowsmentioning
confidence: 99%
“…Intestinal health is the basis for overall pig health, maximum growth performance, and feed utilization efficiency [ 4 ]. However, after sow pregnancy, piglets’ feed intake is usually limited due to insufficient milk production when the sow responds to various stress factors [ 5 ]. The intestines of piglets atrophy and induce intestinal oxidative stress, and the deficiency of various nutrients, including glutamate, leads to a related growth depression syndrome in piglets [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%